2017
DOI: 10.1177/1609406917706883
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in Broker-Facilitated Participatory Cross-Cultural Research

Abstract: Health researchers are increasingly using community-based participatory research approaches because of the benefits accrued through ongoing community engagement. The documentation of our research partnership highlights key ethical and analytical challenges researchers face in participatory research, particularly in projects partnering with service providers or cultural brokers in cross-cultural settings. In this article, we describe how choices made to accommodate a participatory research approach in the exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Meyer et al also discussed the highly participatory approach as challenging, as it requires considerable time, particularly as a bilingual study. 39 These findings accord with experiences by Kowal et al 38 as well as our own. While we also experienced the challenges of demands on time and resources (e.g., time needed for training and mentorship throughout the study period and for knowledge mobilization, costs associated with holding meetings and honoraria for the Brokers), working with the Brokers and (Organization name) allowed more meaningful engagement with communities that was culturally sensitive and accessible to diverse communities.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Meyer et al also discussed the highly participatory approach as challenging, as it requires considerable time, particularly as a bilingual study. 39 These findings accord with experiences by Kowal et al 38 as well as our own. While we also experienced the challenges of demands on time and resources (e.g., time needed for training and mentorship throughout the study period and for knowledge mobilization, costs associated with holding meetings and honoraria for the Brokers), working with the Brokers and (Organization name) allowed more meaningful engagement with communities that was culturally sensitive and accessible to diverse communities.…”
Section: Discussionsupporting
confidence: 92%
“…While the role of community members in linking communities to health services is well established in the literature (as Community/Cultural Brokers, Lay Health Workers, Community Health Workers, etc. ), there is very little documented evidence for their role in health research 38 . Meyer et al have done important work with training community leaders as researchers and engaging lay health educators to reach out to isolated women in a Hispanic community 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the capabilities of individuals, we have stressed the importance of research team composition, polyphony, and practices in the overall understanding and analysis of the research setting. In particular, complex problems often surpass the limited capability of individual researchers and thus require acquisition of knowledge by other researchers, practitioners or research assistants (Van de Ven, 2007, 2018; Avenier and Cajaiba, 2012; Kowal et al ., 2017; Schumacher, 2018). While research has shown how teams can share data gathering work and coordinate data analysis across jurisdictions, boundaries, and fields (Köhler et al ., 2012; Jarzabkowski et al ., 2015; Smets et al ., 2015), we stress the significance of a fit between team capability and research setting complexity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the latter case, the researchers can critically evaluate each others' interpretations, potentially increasing the depth and robustness of the analysis. Such differences in complementary skillsets is also emphasized by Kowal et al (2017) who first used a service provider and later graduate students and postdoctoral fellows as cultural and linguistic brokers. These students and fellows, they argue, had the additional benefits of having formal research training, which fed back into how they assisted in language translation and interpretation.…”
Section: Selection Collection and Analysismentioning
confidence: 99%